2017
DOI: 10.1097/md.0000000000006826
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease is independently associated with hypertension in men

Abstract: Although studies have shown that chronic obstructive pulmonary disease (COPD) and hypertension are linked as comorbidities, it remains unclear whether COPD is independently associated with the risk of hypertension or is caused by common risk factors such as age and smoking. The objective of this study was to investigate the relationship between COPD and hypertension by using nationally representative data.This cross-sectional study analyzed data from the Korea National Health and Nutrition Examination Survey V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…In a recent cross-sectional study, COPD was independently associated with hypertension (OR 1.71, 95% CI 1.37-2.13) after adjusting for age, obesity, smoking status, diabetes, and metabolic syndrome. 25 In another study, half of the patients hospitalized for COPD exacerbation had a previous diagnosis of hypertension. 8 The prevalence of diabetes is also increasing in COPD, particularly in patients with worse lung function.…”
Section: Classical Cardiovascular Risk Factorsmentioning
confidence: 99%
“…In a recent cross-sectional study, COPD was independently associated with hypertension (OR 1.71, 95% CI 1.37-2.13) after adjusting for age, obesity, smoking status, diabetes, and metabolic syndrome. 25 In another study, half of the patients hospitalized for COPD exacerbation had a previous diagnosis of hypertension. 8 The prevalence of diabetes is also increasing in COPD, particularly in patients with worse lung function.…”
Section: Classical Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Studies by other authors have shown that the development of COPD and AH is influenced by such risk factors as age and smoking. In the meantime, a significant relationship was found to exist between COPD and AH, which did not depend on the duration of either disease 34 . Analysis of literature data suggests that patients with COPD and low body mass index are at high risk for bronchial obstruction, osteoporosis, abdominal aorta aneurysm, peripheral vascular disease and substance abuse 35 .…”
Section: Discussionmentioning
confidence: 79%
“…Our study of French women observed no associations between hypertension and all-VTE, but a weak association between hypertension and PE was identified. It is possible that these results could be explained by uncontrolled confounding from conditions such as pulmonary disease (or other respiratory conditions), which could be associated with both hypertension [ 34 ], and the risk of PE [ 35 ]. Similarly, isolated PE has been associated with a higher risk of arterial thrombotic events [ 36 ], which could possibly be explained by underlying hypertension among people with PE as reported in our results.…”
Section: Discussionmentioning
confidence: 99%